Health education interventions for individuals with visual or hearing impairment: a scoping review - Sohyun Jin; Geumbo Ko; Youngshin Song (BMC Public Health)
Abstract Background Visual impairment refers to a deficiency in one or more functions of the visual system, while hearing impairment refers to a loss of auditory function, defined either by its impact on communication and daily activities or by clinical thresholds of hearing ability. Individuals with these disabilities encounter various challenges including limited educational opportunities, restricted access to academic resources, and delays or shortages of support services. This study aimed to provide data for improving the health and well-being of individuals with visual or hearing impairments by analyzing health education interventions using classification criteria of the International Classification of Functioning, Disability and Health (ICF). Methods The scoping review followed Arksey and O’Malley’s methodology and adhered to Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews guidelines, organizing research questions by population, concepts, and contexts. Data included studies on health education interventions for individuals with visual or hearing impairments, sourced from Cochrane, Ovid MEDLINE, and Google Scholar. A specific search strategy with relevant keywords was used. The selection focused on intervention studies evaluating the effects of the intervention for these individuals globally. Two researchers independently reviewed full-text articles and extracted data into a standardized table, with results summarized using descriptive statistics. Results The literature search identified 3,168 articles, 34 of which were selected for analysis (19 concerned individuals with visual impairments, while 15 studies concerned individuals with hearing impairments). Health education interventions for the visually impaired mainly focused on skill acquisition and development, primarily delivered through face-to-face sessions. Healthcare providers predominantly facilitated these interventions within healthcare institutions. Similarly, health education interventions for the hearing impaired primarily focused on acquisition and development, mainly through face-to-face interactions. The dropout rate in the interventions ranged from 0% to approximately 50%. Outcome variables included physical function, psychosocial factors, behavior-related variables, and knowledge-related variables derived from the ICF in both cohorts. Conclusions This scoping review presented an examination of tailored health education interventions for individuals with visual or hearing impairments. Delivered largely through face-to-face sessions by healthcare providers, these interventions focused on skill acquisition and development, addressing physical function, psychosocial factors, behavior-related changes, and knowledge improvements. The wide range of dropout rates revealed barriers such as accessibility and sustainability. These findings emphasize the need for innovation and targeted strategies to improve the effectiveness and inclusivity of health education programs.